The relationship between perfectionism and sleep quality in athletes: the mediating role of mental toughness - Guozhuang Chen; Jiali Qian; Yuhan Qiu; Lei Xu; Kun Wang (BMC Psychology)
Abstract Recent research suggested that mental toughness might play a mediating role in the relationship between multidimensional perfectionism and sleep quality. This study sought to examine the associations between multidimensional perfectionism, mental toughness, and sleep quality in young Chinese athletes, with a particular focus on investigating the potential mediating role of mental toughness in the relationship between multidimensional perfectionism and sleep quality. A total of 208 Chinese athletes (129 females and 79 males) aged from 15 to 29 (Mage = 19.9, SD = 2.52) were included. Structural equation modeling (SEM) was used to analyze the potential mediating effect. The results revealed that perfectionism striving was not associated with sleep quality, whereas perfectionism concerning emerged as a negative predictor of sleep quality. Mental toughness could positively predict sleep quality. The mediation analysis demonstrated that mental toughness partially mediated the relationship between perfectionism concerning and sleep quality. This study revealed that perfectionism concerning can reduce sleep quality, and mental toughness played a partial mediating role in the relationship between perfectionism concerning and sleep quality among Chinese young athletes. These findings suggest that enhancing athletes’ mental toughness and reducing perfectionism concerning may be effective strategies for improving sleep quality.